ANALISIS PENGARUH KREATIVITAS PROGRAM PEMASARAN, HUBUNGAN DENGAN PELANGGAN TERHADAP INOVASI PRODUK SERTA PENGARUHNYA TERHADAP KINERJA PEMASARAN (Studi Kasus Pada UKM Pengolahan Kayu di Kabupaten Rembang) - Malichan Maslichan; Dian Ayu Liana Dewi (BBM (Buletin Bisnis & Manajemen), 2018)
This study aims to analyze the influence of customer relationship to product innovation, the influence of marketing program's creativity toward product innovation, the influence of relationship with customer to the improvement of marketing performance, the influence of marketing program creativity toward the improvement of marketing performance and analyze the effect of product innovation on marketing performance in order to increase marketing performance SMEs processing wood in Rembang regency. The expected target of this research is to get a concrete picture of strategy of improving marketing performance of SMEs of wood processing in Kabupaten Rembang which will be used as a reference for business improvement in SME development. The population of this study includes all actors SMEs Rembang wood processing. Determination of sample in this research is done by random sampling technique by purposive that is selecting wood processing SME with criterion specified. The respondents are the managers or owners of SMEs. Analytical techniques used in this study are the model of causality or influence and relationship. Analyzer used in processing the data to test the hypothesis that is proposed is by using SEM (Structural Equation Model). The result of the research shows that customer relationship has significant effect on product innovation with Standardized coefficient value 0,460. Creative marketing programs also significantly influence product innovation with the value of Standardized coefficient of 0.378. Furthermore, the relationship with the customer also significantly influences the marketing performance improvement with the value of Standardized coefficient of 0.264 as well as the creativity of the marketing program is also significant to the improvement of marketing performance with the value of standardized coefficient of 0.514. For product innovation also have an effect not significant to increase marketing performance with standardized coefficient value 0,183. Kata Kunci: marketing performance, innovation, marketing creativity, dan customer relationship